Hölderlin e l’immagine socchiusa. Riflessioni sul frammento «Und der Himmel wird…» dello ‘Homburger Folioheft’ tra materialità, divino e segno (Studia theodisca, 2025)
The aim of this contribution is to analyse the fragment «Und der Himmel wird…» on page 40 of the Homburger Folioheft, paying particular attention to the notion of the ‘immagine socchiusa’ (slightly closed image). This expression highlights the tension between open and closed, between revealed and veiled, within Hölderlin’s work. The fragment is not written with ink but directly engraved on the paper. This technique invites us to reflect on the choice of medium and material. Furthermore, the theme of the sky, mentioned on page 40, connects the notion of the open with the dimension of the divine. This becomes represented as an invisible being seeking to manifest itself. The influence of Heinse will also be examined, as it is fundamental for understanding the connection between sign, painting, and the divine.